A Pharmacokinetic Analysis and Pharmacogenomic Study of 6-mercaptopurine - Vicha A; Katsila T; Giannopoulou E; Leontari H; El Mubarak M; Gravia A; Chondrou V; Symeonidis A; Patrinos GP; Kalofonos HP; Sivolapenko G (International Journal of Pharmaceutical Sciences and Developmental Research - Peertechz Publications, 2015)
Background: The efficacy and safety of 6-mercaptopurine (6-MP) therapy rely on the concentration of its metabolites. The aim of the current study is the pharmacokinetic analysis of 6-MP and the detection of its metabolites as well as the role of Thiopurine S-methyl transferase (TPMT), the enzyme associated with 6-MP metabolism, as a pharmacogenomics biomarker. Materials and Methods: Data were collected from 19 patients with different types of leukemia and lymphoma who received 6-MP chemotherapy. Pharmacokinetic analysis was performed using an HPLC. The VNTR promoter polymorphisms of TPMT were detected. Results and Conclusion: The pharmacokinetic analysis confirmed the heterogeneity of the 6-MP metabolism. The TPMT genotyping revealed a correlation between the TPMT*3C variant and increased levels of 6-thioguanine nucleotides (TGs). No methylation pattern was obtained.